A case of Severe Low-dose Methotrexate-induced Toxicity - Filiz Topaloğlu Demir (Haseki Tıp Bülteni, 2016)
Methotrexate (MTX) is an antimetabolite which competitively inhibits dihydrofolic acid reductase; inhibits purine and thymidylic acid synthesis, which in turn interferes with DNA synthesis, repair, and cellular replication. MTX is a good treatment option for neoplastic, rheumatic and dermatological diseases. However, rarely, may cause side effects, such as agranulocytosis and bone marrow suppression, mucosal tissue inflammation and necrotic changes, liver cell necrosis and hepatic cirrhosis, pulmonary fibrosis, and severe renal dysfunction. Herein, we report a 67-year-old female patient with a history of psoriasis for 15 years and MTX 15 mg/sc/week use for 8 years who was admitted due to the complaints of pancytopenia, mucositis and ulcers on psoriatic plaques despite low-dose MTX use. We present this case to remind that MTX toxicity might occur with low-dose MTX usage and to draw attention to various factors that facilitate the low-dose MTX toxicity, such as age, renal insufficiency, low albumin levels, infections, proton pump inhibitors and non-steroidal anti-inflammatory drugs.